Industry influence over global alcohol policies via the World Trade Organization: a qualitative analysis of discussions on alcohol health warning labelling, 2010–19. Issue 3 (March 2022) - Barlow, Pepita; Gleeson, Deborah; O'Brien, Paula; Labonte, Ronald
Summary: Background: Accelerating progress to implement effective alcohol policies is necessary to achieve multiple targets within the WHO global strategy to reduce the harmful use of alcohol and the Sustainable Development Goals. However, the alcohol industry's role in shaping alcohol policy through international avenues, such as trade fora, is poorly understood. We investigate whether the World Trade Organization (WTO) is a forum for alcohol industry influence over alcohol policy. Methods: In this qualitative analysis, we studied discussions on alcohol health warning labelling policies that occurred at the WTO's Technical Barriers to Trade (TBT) Committee meetings. Using the WTO Documents Online archive, we searched the written minutes of all TBT Committee meetings available from Jan 1, 1995, to Dec 31, 2019, to identify minutes and referenced documents pertaining to discussions on health warning labelling policies. We specifically sought WTO member statements on health warning labelling policies. We identified instances in which WTO member representatives indicated that their statements represented industry. We further developed and applied a taxonomy of industry rhetoric to identify whether WTO member statements advanced arguments made by industry in domestic forums. Findings: Among 83 documents, comprising TBT Committee minutes, notifications to the WTO of the policy proposal, and written comments by WTO members, WTO members made 212 statements (between March 24, 2010, and Nov 15, 2019) on ten alcohol labelling policies proposed by Thailand, Kenya, the Dominican Republic, Israel, Turkey, Mexico, India, South Africa, Ireland, and South Korea. WTO members stated that their claims represented industry in seven (3·3%) of 212 statements, and 117 (55·2%) statements featured industry arguments. Member statements featured many arguments used by industry in domestic policy forums to stall alcohol policy. Arguments focused on descaling and reframing the nature and causes of alcohol-related problems, promoting alternative policies such as information campaigns, promoting industry partnerships, questioning the evidence, and emphasising manufacturing and wider economic costs and harms. Interpretation: WTO discussions at TBT Committee meetings on alcohol health warnings advanced arguments used by the alcohol industry in domestic settings to prevent potentially effective alcohol policies. WTO members appeared to be influenced by alcohol industry interests, although only a minority of challenges explicitly referenced industry demands. Increased transparency about vested interests might be needed to overcome industry influence. Funding: None.